Mir15a/mir16‐1 cluster and its novel targeting molecules negatively regulate cardiac hypertrophy. Issue 8 (15th December 2020) - Guo, Hongchang; Ma, Ke; Hao, Wenjing; Jiao, Yao; Li, Ping; Chen, Jing; Xu, Chen; Xu, Fu‐jian; Lau, Wayne Bond; Du, Jie; Ma, Xin‐liang; Li, Yulin
Abstract: In response to pathological stimuli, the heart develops ventricular hypertrophy that progressively decompensates and leads to heart failure. miRNAs are increasingly recognized as pathogenic factors, clinically relevant biomarkers, and potential therapeutic targets. We identified that mir15a/mir16‐1 cluster was negatively correlated with hypertrophic severity in patients with hypertrophic cardiomyopathy. The mir15a/mir16‐1 expression was enriched in cardiomyocytes (CMs), decreased in hypertrophic human hearts, and decreased in mouse hearts after transverse aortic constriction (TAC). CM‐specific mir15a/mir16‐1 knockout promoted cardiac hypertrophy and dysfunction after TAC. CCAAT/enhancer binding protein (C/EBP)β was responsible for the downregulation of mir15a/mir16‐1 cluster transcription. Mechanistically, mir15a/mir16‐1 cluster attenuated the insulin/IGF1 signal transduction cascade by inhibiting multiple targets, including INSR, IGF‐1R, AKT3, and serum/glucocorticoid regulated kinase 1 (SGK1). Pro‐hypertrophic response induced by mir15a/mir16‐1 inhibition was abolished by knockdown of insulin receptor (INSR), insulin like growth factor 1 receptor (IGF1R), AKT3, or SGK1. In vivo systemic delivery of mir15a/mir16‐1 by nanoparticles inhibited the hypertrophic phenotype induced by TAC. Importantly, decreased serum mir15a/mir16‐1 levels predicted the occurrence of left ventricular hypertrophy in a cohort of patients with hypertension. Therefore, mir15a/mir16‐1 cluster is a promising therapeutic target and biomarker for cardiac hypertrophy. Abstract : mir15a/mir16‐1 cluster exerts protective effects against the progression of the cardiac hypertrophy and dysfunction (left). During hypertrophic stress, increased C/EBPβ downregulates the mir15a/mir16‐1 cluster, resulting in up‐regulation of multiple target proteins (INSR, IGF1R, AKT3, SGK1) in cardiomyocytes, causing increased activation of insulin/IGF1 signaling, ultimately causing cardiac hypertrophy and dysfunction. The CHO‐PEGA delivery system replenishes mir15a/mir16‐1 in the heart, attenuating cardiac hypertrophy and heat failure (right). Meanwhile, reduced circulating mir15a/mir16‐1 levels are associated with the hypertrophic degree and cardiac hypertrophy risk in patients (bottom).